KEPRAKTISAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNANAKAN GEOGEBRA PADA SUB POKOK BAHASAN GARIS SINGGUNG PERSEKUTUAN DUA LINGKARAN - Elok Rohmawati (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2017)
The purpose of this research is to know the practicality of learning media of mathematics using Geogebra on sub subject of tangent alliance of two circles. Practicality seen from the questionnaire ease of using Geogebra, questionnaire results minimize the role of teachers, and the results of the observation sheet minimizes the role of teachers. Based on the results of experimental learning media, questionnaire ease using Geogebra states media easy to use, questionnaires teacher role minimization and observation sheet minimize the role of teachers said the media can minimize the role of teachers. Thus, the mathematics learning medium using Geogebra on the sub-subject of the two-circle fellowship can be stated as practical. The practicality of this medium indicates that this medium can be used in assisting the teacher to explain the tangent material of the two-circle fellowship and can be used by the students to study the concept of tangent to the two-circle alliance.